Design and fabrication of a self-balancing device for food delivery / Alif Darwisy Mohd Fauzi, Nur Kamarliah Kamardin and Ahmad Idzwan Yusuf - Mohd Fauzi, Alif Darwisy; Kamardin, Nur Kamarliah; Yusuf, Ahmad Idzwan (School of Mechanical Engineering, 2023)
This is also influenced by the Grab application in Malaysia which introduced jobs such as Grab drivers and Grab delivery riders. The Grab delivery riders are the ones responsible to deliver food to customers that requested food delivery through the Grab application. Unfortunately, accidents tend to happen where the food and beverage inside the delivery are often spilled and damaged. This is because the items are not anchored properly and lose balance when the rider is weaving their bike especially when it is a rushed delivery. The self-balancing device for food delivery is the solution to the problem as it could help counter the loss of balance to maintain the positioning of the food inside the delivery bag so that the customer will receive their meal in a good condition